Evaluating critical success factors and level of challenges in project life cycle (PLC) - Hassan, Sallaudin; Farhana, Natasha; Aishah, Siti; Mahirah, Siti; Firdaus Jimisiah. J, Khairul (International Journal of Engineering and Technology, 2018)
This research aims to evaluate the Critical Success FactorsÂ (CSF) of project management and Â to assess the level of challenges at each steps in Project Life Cycle (PLC). Five Independent Variable (IV) Â is been selected as Critical Success Factors which is Leadership, Effective Communication, Teamwork, Â Organization and Project Nature. There are four main stage in project which is Defining, Planning, Â Executing and Closure. The scope of this research is on projects/eventsÂ Â conducted under Student Â Development and Campus Life Style (SDCL). Five projects has been selected for assessment in thisÂ research.Â Survey questionnaire is been used as primary data collection. LIKERT Scale is been used to rank the answer from respondents. 50 respondents are involve in this research. Data is analyzed by using SPSS version 21. Result shows that the most critical success factors in project is Team Work while the least Critical Success Factor is Leadership. Meanwhile, the most challenges stage in project management is Executing, while the least challenges stage is Defining. The finding in this research is considered important discovery. More efforts should be focus on identified Critical Success Factor and the most challenges stage in Project Life Cycle.Â It is suggested that the scope of study to be extended to other universities or industries in future research.Â Â